Our methods of surgical training for young ear surgeons: how to teach comprehensive knowledge in radiological image and surgical anatomy of the temporal bone - Ito, Taku; Kitamura, Ken; Tsunoda, Atsunobu; Kishimoto, Seiji (Otology Japan, 2012)
For the purpose of effective instruction of ear surgery, we made an educational progrum for young ear surgeons. This program is aimed to establish the knowledge of temporal bone anatomy with reference to radiological images, especilally computed tomography (CT). Dicom data of temporal bone CT taken from healthy adult subject on 0.167 mm slice thickness are supplied to trainees. Trainees can observe each slices on their personal computer. Then, each structures in the temporal bone, such as the eustacian tube, ossicles, vessels, facial nerves, labyrinth, etc., are observed on cosecutive images. Through this progrum, trainees can study three-dimensional anatomy of the temporal bone elsewhere. Trainees also experience a cadaver dissection and study an appropriate use of the microscope and drill. After these experience, trainee can perform ear surgery. Their manupilation are recorded on video and trainee must review and edit briefly. This video recording and editing are also instructive for trainees. The program also containes partcipation to the lateral skull base surgery which is useful in recognition of through temporal bone anatomy. We believe, our progrum is complehensive and wothry for education in ear specialists.